Mesenchymal Stem Cells Role in COVID-19 Myocardial Injury - Triya Damayanti; Mega Juliana; Yasmina Hanifah; Erlina Burhan; Putri Suci Ramadhany (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Coronavirus Disease-19 (COVID-19) has become a global pandemic that affected the lives of billion individuals. The clinical spectrum of the disease varies from asymptomatic form to severe manifestation in term of acute respiratory distress syndrome (ARDS), shock and septic shock and multiple organ dysfunction syndrome (MODS). Clinical studies have also reported an association between COVID-19 and cardiovascular manifestation, such as myocardial injury, arrhythmias, acute coronary syndrome (ACS) and thromboembolism. Myocardial injury has been reported frequently and is associated with high mortality. The currently approved strategies for COVID-19 are supportive rather than curative treatment. Cell-based approaches, primarily using mesenchymal stem cell (MSC) has demonstrated safety and possible efficacy as an adjuvant therapy in COVID-19 patient. Mesenchymal stem cells have shown important role in the therapy of cardiovascular disease due to their prominent features including their ability to differentiate into cardiovascular cells, immunomodulatory properties, antifibrotic activity and ability to undergo neovasculogenic.